PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, LOKASI DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI CHEZZ CAFENET - Maria Yalinta Ena; Antonio E.L. Nyoko; Wehelmina M Ndoen (Universitas Nusa Cendana, 2019)
This study aims to determine: (1) the influence of price perception on purchasing decisions (2) the influence of service quality on purchasing decision (3) the influence of location on purchasing decision (4) the influence of word of mouth on purchasing decision and (5) the influence of Price Perception, Service Quality, Location, Word of Mouth to purchase decision on customers CafeNet. This study uses a quantitative method approach. The population in this study are consumers who have made purchases in CafeNet-Central Kupang. The sampling technique is probability sampling with the number of samples of 97 people. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis technique using multiple regression. The results showed that: (1) Price Perception had a significant effect on Purchasing Decision; (2) Service Quality did not had a significant effect on Purchasing Decision; (3) The Location did not had a significant effect on Purchasing Decisions; (4) The Word of Mouth did not had a significant effect on Purchasing Decisions; and (5) The Price Perception, Service Quality, Location and Word of Mouth did not had a significant effect simultaneously to Purchase Decision on CafeNet customer- Central Kupang. Keywords: Price Perception, Service Quality, Location, Word of Mouth, and Purchase Decision.